2008
DOI: 10.2528/pierb07102903
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Omnidirectional Reflection in Photonic Crystal Heterostructures

Abstract: Abstract-In this paper we have theoretically studied the omnidirectional total reflection frequency range of a multilayered dielectric heterostructures. Three structures of Na 3 AlF 6 /Ge multilayer have been studied. The thickness of the two layers of the first and second structure is differing from each other and the third photonic structure is the combination of first and second structures. Using the Transfer Matrix Method (TMM) and the Bloch theorem, the reflectivity of one dimensional periodic structure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…It was shown that a one-dimensional photonic crystal (1DPC) composed of alternating slabs of ordinary double-positive (DPS) and DNG media can have a type of photonic bandgap (PBG) corresponding to zero averaged refractive index (n) [9][10][11][12]. Moreover, it is well known that a 1DPC constituted by a periodic repetition of MNG and ENG layers can possess another type of photonic gap with effective phase (ϕ eff ) of zero [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a one-dimensional photonic crystal (1DPC) composed of alternating slabs of ordinary double-positive (DPS) and DNG media can have a type of photonic bandgap (PBG) corresponding to zero averaged refractive index (n) [9][10][11][12]. Moreover, it is well known that a 1DPC constituted by a periodic repetition of MNG and ENG layers can possess another type of photonic gap with effective phase (ϕ eff ) of zero [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a considerable increase in research interest directed towards the development of optoelectronic devices based on quantum well heterostructures [20][21][22][23], guided wave devices [24][25][26] and quantum nanostructures [27,28]. To understand the physical properties of device structures, it is important to simulate the expected performance on a computer.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Gradient-index optical materials have been used to fabricate interference filters [1,2] and environment sensors [10], and potential applications such as broadband laser protection eyewear and spectral beam splitter have also been demonstrated [11][12][13]. Many applications based on 1D photonic crystals are formed by repeating two or more distinct homogeneous dielectric layers with different refraction indices [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]; however, studies on 1D periodic dielectric structures with smoothly varying refraction index are still valuable, because of advantages such as reduced optical losses and better mechanical properties in contrast to discrete multilayer structures [13,[34][35][36][37]. To enlarge the omnidirectional photonic band gap, porous silicon dielectric mirrors formed by a periodic repetition of a Gaussian profile refractive index have been developed [8,9].…”
Section: Introductionmentioning
confidence: 99%